Limiting parametersof deuterium-tritium plasma in medium size tokamak with high-power injection heating - Aльмaгaмбетов А.Н.; Чирков, А.Ю. (Recent Contributions to Physics, 2016)
Fusion systems with low plasma power gain factor Q 1 can be considered as controlled source of fusion neutrons for a hybrid fusion-fission reactors. Significant population of fast ions can be supported by a powerful neutral beam injection in regimes with Q 1. The reaction rate for fast ions greatly exceeds the rate for thermal Maxwellian ions. Present day magnetic fusion devices can be considered as prototypes ofsuch systems. The possible ranges of the neutron source parameters are discussed for medium size tokamaks (plasma radius of 0.5 to 1 m). Thepossibility of regimes with Q 1 is justified.